On the sheaf of modules - (:unkn) unknown (TAYLOR & FRANCIS INC, 2005)
Let M be an R-module and let X = Spec(M) be all prime submodules of M. We obtain an R-module Ox(U) for each open set U in X. We show that Ox is a sheaf of R-modules over X.
Keywords: prime submodule; Zariski topology; SPECTRUM